Desirable characteristics of casein peptides with simultaneously enhanced emulsion forming ability and antioxidative capacity in O/W emulsion. (October 2022) - Yu, Chunyan; Zheng, Lin; Cai, Yongjian; Zhao, Qiangzhong; Zhao, Mouming
Abstract: This study aimed to explore the desirable characteristics of casein hydrolysates with simultaneously enhanced emulsion forming and antioxidative ability in oil-in-water (O/W) emulsion. Effects of physicochemical properties of casein hydrolysates prepared by trypsin, alcalase, and neutrase on physical and oxidative stability of O/W emulsion were studied, and potential antioxidant peptides were characterized by UPLC-MS/MS and bioinformatics analysis. Results showed that casein hydrolysates at a lower degree of hydrolysis (DH) produced by trypsin displayed higher zeta potential absolute values (−31.7 mV), smaller particle size (170.75 nm) and improved antioxidant properties compared to alcalase and neutrase, and could form more stable emulsion with d4, 3 of 0.39–0.41 μm at a broader range of DH. Additionally, compared with sodium caseinate (NaCas), the oxidation of emulsion was significantly retarded during the storage progress prepared by the trypsin hydrolysates at DH of 4.49% alone or with Tween 20. Peptidomics indicated that the trypsin hydrolysates contained more peptides with basic amino acids at C-terminal and aromatic amino acids at N-terminus, which exhibited cationic amphiphilic properties with grand average of hydrophilicity values (GRAVY) of −0.5 ∼ +0.5 and pI > pH 7.0. This could contribute to their better emulsion formation and inhibition of lipid oxidation ability by producing dense interfacial layers with peptides interactions or excluding metal ions in O/W emulsions. These results suggested that casein hydrolysates at lower DH prepared by trypsin owned potential amphiphilic antioxidant peptides, which were desired to enhance the stability and functional activity of O/W emulsion. Graphical abstract: Image 1 Highlights: Trypsin hydrolysates featured specificity in zeta value and particle size at low DH. Casein hydrolysates exhibited better emulsion formation ability at low DH. Trypsin hydrolysates at low DH effectively retarded lipid oxidation. More cationic amphiphilic peptides were observed in trypsin hydrolysates.